Dissipation of some citrus selective residual herbicides in an irrigation well. - Gómez-De-Barreda, Diego; Gamón Vila, Miguel; Lorenzo Rueda, Elena; Saez Olmo, A.; Garcia de la Cuadra, J.; Ten, A.; Peris-Ribera, Cristòfol (2017)
The aim of this work was to study the behaviour of some of the main citrus selective residual herbicides in the water of an irrigation well. The chemicals used were: atrazine, simazine, terbuthylazine, terbutryn, terbumeton, bromacil and diuron. The simetric triazines and bromacil were analyzed by gas chromatography and diuron by HPLC. The mentioned pesticides were introduced in the well in order to simulate a point-source contamination. Levels of contamination of the well due to herbicide application were about 1 mg/l, however, dissipation of the herbicides was almost complete 8 days after application, except for bromacil and diuron which persisted longer than the s-triazines.